Modelling the transport of sloughed cladophora in the nearshore zone of Lake Michigan. (1st December 2022) - Shen, Chunqi; Liao, Qian; Bootsma, Harvey A.; Lafrancois, Brenda Moraska
Abstract: The invasion of dreissenid mussels has profoundly altered benthic physical environments and whole-lake nutrient cycling in the Great Lakes over the past several decades. The resurgence of the filamentous green alga Cladophora appears to be one of the consequences of this invasion. Sloughed Cladophora deteriorates water quality, fouls recreational beaches, and may contribute to outbreaks of avian botulism, which have been especially severe in the Sleeping Bear Dunes National Lakeshore (SLBE) region of Lake Michigan. To help determine the fate of sloughed Cladophora, a Lagrangian particle trajectory model was developed to track the transport of Cladophora fragments in the nearshore zone based upon a physical transport-mixing model. The model results demonstrate that the primary deposition sites of sloughed Cladophora within the SLBE region are mid-depth sites not far away from their initial growth area. Because of high algae production in the nearshore waters and limited exchange between the inner and outer bay, the shoreline beach of Platte Bay appears to be particularly vulnerable to fouling, with overall three times as many accumulated particles as those along the Sleeping Bear Bay and Good Harbor Bay. The results of this model may be used to guide regional environmental management initiatives and provide insights into the mechanisms responsible for avian botulism outbreaks. This model may also inform the development of whole-lake ecosystem models that account for nearshore-offshore interactions. Graphical abstract: Image 1 Highlights: An understanding of mechanisms regulating the transport of Cladophora is imperative. A particle trajectory model was used to track the transport of detached Cladophora. The mid-depth regions are the potential hotspots for Cladophora to accumulate.